2010
DOI: 10.1177/0305735610362821
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the discrete and dimensional models of emotion in music

Abstract: The primary aim of the present study was to systematically compare perceived emotions in music using two different theoretical frameworks: the discrete emotion model, and the dimensional model of affect. A secondary aim was to introduce a new, improved set of stimuli for the study of music-mediated emotions. A large pilot study established a set of 110 film music excerpts, half were moderately and highly representative examples of five discrete emotions (anger, fear, sadness, happiness and tenderness), and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
532
5
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 508 publications
(637 citation statements)
references
References 75 publications
43
532
5
18
Order By: Relevance
“…While a growing body of research has explored the brain substrates of musical emotions, so far the implicit processing of emotions in music has remained neglected despite music often being used as an accompaniment to another activity. Behavioral data confirmed that even when shortened, the music soundtrack clips from the database by Eerola et al (2011) were able to convey sad, fearful, and happy emotions. In implicit compared to explicit processing, we found large cortical areas of activity in the temporal, frontal, and parietal lobes as well as in reward-related areas.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…While a growing body of research has explored the brain substrates of musical emotions, so far the implicit processing of emotions in music has remained neglected despite music often being used as an accompaniment to another activity. Behavioral data confirmed that even when shortened, the music soundtrack clips from the database by Eerola et al (2011) were able to convey sad, fearful, and happy emotions. In implicit compared to explicit processing, we found large cortical areas of activity in the temporal, frontal, and parietal lobes as well as in reward-related areas.…”
Section: Discussionmentioning
confidence: 63%
“…The stimuli were musical excerpts taken from a movie soundtrack database; the music clips in this database were previously rated on a wide range of affective categories and validated for their target emotion (Eerola et al, 2011). Film music stimuli were chosen for this study because music in movies is composed to represent and induce emotions in listeners.…”
Section: Stimulimentioning
confidence: 99%
See 3 more Smart Citations